The Process of Steel Manufacturing: Techniques, Technologies, and Environmental Impacts (Global Scientific Review, 2023)
Steel manufacturing is among the world's largest industries, with millions of tons of steel produced every year. This study aimed to analyze the steel manufacturing process, discuss the technological techniques utilized, evaluate the environmental impact of this industry, and assess the current state of steel manufacturing in Uzbekistan.